Supply chain management and practices of firm performance: A review paper - Halbusi, Hussam Al; Tehseen, Shehnaz * (SIATS Journals, 2018)
Objective: The aim of this study is to discover the components of green supply chain management (GSCM) practices and their outcome in terms of economic performance, environmental performance, and social performance. Methods: Researchers have performed a focused search for articles on (1) green supply chain management (GSCM) practices (2) economic performance, environmental performance, and social performance, in four major databases: Web of Science, Science Direct, IEEE Xplore and Scopus. Those databases are deemed broad enough to cover both green supply chain management and outcomes performances literature. Results: The final set included 80 articles. Most articles are reviewed and surveys that refer to actual literature to describe green supply chain management for a specific specialty, or purpose; or to provide a general overview of the green supply chain management. Another group carried various studies, from evaluation of its performances. Conclusions: Research on green supply chain management (GSCM) is active and various. We hope that this survey contribute to the understanding of the available options, and for other researchers to join this line of research.